Lactobacillus johnsonii N6.2 and Blueberry Phytophenols Affect Lipidome and Gut Microbiota Composition of Rats Under High-Fat Diet - Teixeira, Leandro Dias; Torrez Lamberti, Monica F.; DeBose-Scarlett, Evon; Bahadiroglu, Erol; Garrett, Timothy J.; Gardner, Christopher L.; Meyer, Julie L.; Lorca, Graciela L.; Gonzalez, Claudio F. (Frontiers in Nutrition, 2021)
Obesity is considered a primary contributing factor in the development of many diseases, including cancer, diabetes and cardiovascular illnesses. Phytochemical-rich foods, associated to healthy gastrointestinal microbiota, have been shown to reduce obesity and associated comorbidities. In the present article, we describe the effects of the probiotic Lactobacillus johnsonii N6.2 and blueberry extracts (BB) on the gut microbiota and lipid profile of rats under a high-fat (HF) or low-calorie (LC) diet. L. johnsonii was found to increase the levels of long chain fatty acids (LCFA) in the serum of all animals under HF diet, while reduced LCFA concentrations were observed in the adipose tissue of animals under HF diet supplemented with BB extracts. All animals under HF diet also showed lower protein levels of SREBP1 and SCAP when treated with L. johnsonii. The gut microbiota diversity, β-diversity was significantly changed by L. johnsonii in the presence of BB. A significant reduction in α-diversity was observed in the ileum of animals under HF diet supplemented with L. johnsonii and BB, while increased α-diversity was observed in the ilium of animals under LC diet supplemented with L. johnsonii or BB. In summary, L. johnsonii and BB supplementation induced significant changes in gut microbiota diversity and lipid metabolism. The phospholipids pool was the lipidome component directly affected by the interventions. The ileum and colon microbiota showed clear differences depending on the diet and the treatments examined.